Atomic‐Scale Modulation of Synthetic Magnetic Order in Oxide Superlattices. Issue 2 (23rd December 2022) - Jeong, Seung Gyo; Song, Sehwan; Park, Sungkyun; Lauter, Valeria; Choi, Woo Seok
Abstract: Atomic‐scale precision control of magnetic interactions facilitates a synthetic spin order useful for spintronics, including advanced memory and quantum logic devices. Conventional modulation of synthetic spin order has been limited to metallic heterostructures that exploit Ruderman–Kittel–Kasuya–Yosida interaction through a nonmagnetic metallic spacer; however, they face issues arising from Joule heating and/or electric breakdown. The practical realization and observation of a synthetic spin order across a nonmagnetic insulating spacer will lead to the development of spin‐related devices with a completely different concept. Herein, the atomic‐scale modulation of the synthetic spiral spin order in oxide superlattices composed of ferromagnetic metal and nonmagnetic insulator layers is reported. The atomically controlled superlattice exhibits an oscillatory magnetic behavior, representing the existence of a spiral spin structure. Depth‐sensitive polarized neutron reflectometry evidences modulated spiral spin structures as a function of the nonmagnetic insulator layer thickness. Atomic‐scale customization of the spin state can move the field one step further to actual spintronic applications. Abstract : Atomic‐scale precision epitaxy and microscopic observation let us customize the synthetic magnetic order, useful for spintronic applications. However, conventional approaches have been limited to metallic heterostructures. Here, atomic‐scale modulation of the synthetic magnetic order is reported across the insulating spacer, observed by a polarized neutron reflectometer. This approach can yield novel controllability of the magnetic order across insulating spacers.